Pestrost lesnatih rastlin na ploskvah za spremljanje stanja gozdov v Sloveniji - Kutnar, Lado (Gozdarski vestnik, 2011)
Based on the assessment of ground vegetation on the monitoring plots of a systematic grid (16 * 16 km) of Level I and on Intensive Monitoring plots of Level II the diversity of woody plant species was analyzed. In different vertical layers of 50 plots we found a total of 102 woody species, of which 46were tree species, and 56 species of shrubs and woody climbers. On average, 15 woody species were recorded per plot, among them 8 tree species. The most frequently assessed tree species were Fagus sylvatica, Picea abies, Acer pseudoplatanus, Quercus petraea, Prunus avium, Abies alba, Carpinus betulus, Fraxinus excelsior, Sorbus aucuparia in Sorbus aria. Among shrub species and woody climbers Rubus hirtus, Hedera helix, Corylus avellana, Daphne mezereum, Clematis vitalba, Sambucus nigra, Rosa arvensis, Euonymus europaea in Rubus idaeus were prevailing. Based on the ordination analyse of the monitoring plots it was proved that the specific woody species composition is characteristic for the particular ecological, site, and forest-stand conditions.
Keywords: gozdovi; vegetacija; lesnate rastline